Pengaruh Kecanggihan Teknologi Informasi, Budaya Organisasi, Dan Kemampuan Teknik Personal Terhadap Efektivitas Sistem Informasi Akuntansi Pada Koperasi Serba Usaha Di Kecamatan Sukawati - Ni Made Listya Ari; Sang Ayu Putu Arie Indraswarawati; Cokorde Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
Information systems play an important role in accounting, because basically accounting must provide accurate information to decision makers. This study aims in this study to determine the effect of sophistication of information technology, organizational culture and personal technical capabilities on the effectiveness of accounting information systems. The population in this study were employees of the Multipurpose Cooperative in Sukawati District with the sample used as many as 95 respondents. The data analysis technique used in this research is multiple linear regression, coefficient of determination, F test and t test. Based on the results of the study, it can be seen that: (1) the sophistication of tax information technology has a positive and significant effect on the effectiveness of accounting information systems, where the regression coefficient is 0.460 and sig 0.000. (2) organizational culture has a significant positive effect on the effectiveness of accounting information systems, where the regression coefficient is 0.250 and sig 0.002. (3) the ability of personal techniques has a significant positive effect on the effectiveness of accounting information systems, where the regression coefficients are 0.231 and sig 0.003. The magnitude of the influence of independent variables on the effectiveness of accounting information systems is 60%. Suggestions that can be given by researchers are Multipurpose Cooperatives in Sukawati District in increasing the tendency of the effectiveness of accounting information systems to always increase the sophistication of information technology, organizational culture and personal technical abilities.Information Technology Sophistication